THE POTENTIAL OF SMARTPHONE TECHNOLOGY FOR ADULT LITERACY DEVELOPMENT IN NIGERIA: OPPORTUNITIES, CHALLENGES, AND STRATEGIES - BABANZARA , UMMU HASSAN (Sokoto Educational Review, 2025)
This paper explores the transformative potential of smartphone technology for adult literacy development in Nigeria, addressing opportunities, challenges, and strategic integration. Despite widespread smartphone penetration offering unique educational avenues, a significant portion of Nigerian adults still face low literacy levels due to traditional barriers like limited access to learning centers, inadequate materials, and rigid curricula. Smartphones, acting as portable mini-computers, can overcome these hurdles by providing access to diverse educational applications, e-books, and multimedia content, facilitating personalized and self-directed learning, and fostering virtual learning communities. While the promise is substantial, challenges include the digital divide, lack of digital literacy, and infrastructure limitations. The paper examines existing initiatives, best practices, and innovative strategies for leveraging smartphones, emphasizing the redefined roles of educators as facilitators. It suggests policy interventions for seamless integration, including subsidies for devices, comprehensive digital literacy training, and the development of culturally relevant content. Ultimately, integrating smartphone technology into Nigeria's national adult literacy framework is crucial for empowering adults and driving national development in the 21st century. DOI: https://doie.org/10.10318/SER.2025120090